Training antenatal care providers to deliver brief problem-solving therapy in rural Ethiopia: a developmental evaluation - Roxanne C Keynejad; Adiyam Mulushoa; Tesera Bitew; Louise M. Howard; Charlotte Hanlon; Sharon Markless (SSM - Mental Health)
Background: Task-sharing is the redistribution of tasks usually performed by specialists, to staff with less training and fewer qualifications. Despite the established clinical efficacy of task-shared brief psychological interventions in low and middle-income countries, training and supervision models are infrequently reported and rarely evaluated. Methods: From the interpretive paradigm, we conducted a developmental evaluation of training, supervision, and task-sharing of antenatal care providers (ANCPs) to deliver problem-solving therapy for antenatal depression in rural Ethiopia. We triangulated 18 qualitative interviews with women intervention recipients, ANCPs, mental health specialist trainer/supervisors and research staff, with documentary data. We employed reflexive thematic analysis before ‘peer review’ of our interpretations by a female Ethiopian research assistant. Findings: Four over-arching themes encompassed the developmental journey, impacts, factors influencing success, and improvements. The complex adaptive healthcare system exerted unforeseen effects on the iterative development of training, supervisory and task-sharing plans. High quality communication skills (‘common elements’) training was most valued by ANCPs, while women especially appreciated psychological intervention ‘specific elements.’ An apprenticeship cascade model could balance the need for frequent, in-person specialist supervision against logistical barriers to travel from the capital. Fostering peer ‘communities of practice’ could support ANCPs' well-being and enhance their continued professional development. Conclusions: This study contributes to sparse literature evaluating task-sharing training and supervisory approaches in resource-restricted settings, from an interpretive paradigm. Developmental evaluation proved a flexible methodological approach for exploring perspectives of stakeholders occupying diverse roles. We demonstrate the importance of embedding in-depth pedagogical consideration and qualitative evaluation into trials which depend on high quality clinical education.